(3GdYdGbGJ GdEbJUGOjI GdOhdjI (B:s (3aj XdGd GdCReI GdEbJUGOjI GdYGdejI (B/s - (3YHO GdSdGe, QVGs ((3GdefUhQI(B: s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B, s, 2011)
(3JWhQ GdfXQI ddYdGbGJ GdEbJUGOjI GdOhdjI(B- (3GdfXQjGJ GdeaSQI ddYdGbGJ GdEbJUGOjI GdOhdjI(B- (3GdSjGSGJ GdJLGQjI heSJbHdgG aj Xd GdCReI GdYGdejI GdQGgfI(B-(3SYQ GdUQa heYjGQ GdOhdGQ(B- (3ejRGf GdeOahYGJ(B- (3GdBdjGJ GdMGceI ddYdGbGJ GdEbJUGOjI GdOhdjI(B- (3GdEJMGOGJ GdEbJUGOjI GdEbdjejI(B- (3GdTQcGJ GdOhdjI hGdYhdeI(B- (3GdCReI GdEbJUGOjI GdYGdejI GdQGgfI, GdLPhQ hGdJHYGJ hJUhQGJ GdEbJUGO eG HYO GdCReIs
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdYdGbGJ GdEbJUGOjI GdOhdjIs